Understanding and eliminating hysteresis for highly efficient planar perovskite solar cells - Wang, Changlei; Xiao, Chuanxiao; Constantinou, Iordania (Advanced energy materials, 2017)
Through detailed device characterization using cross-sectional Kelvin probe force microscopy (KPFM) and trap density of states measurements, we identify that the J-V hysteresis seen in planar organic-inorganic hybrid perovskite solar cells (PVSCs) using SnO2 electron selective layers (ESLs) synthesized by low-temperature plasma-enhanced atomic-layer deposition (PEALD) method is mainly caused by the imbalanced charge transportation between the ESL/perovskite and the hole selective layer/perovskite interfaces. We find that this charge transportation imbalance is originated from the poor electrical conductivity of the low-temperature PEALD SnO2 ESL. We further discover that a facile low-temperature thermal annealing of SnO2 ESLs can effectively improve the electrical mobility of low-temperature PEALD SnO2 ESLs and consequently significantly reduce or even eliminate the J-V hysteresis. With the reduction of J-V hysteresis and optimization of deposition process, planar PVSCs with stabilized output powers up to 20.3% are achieved. The results of this study provide insights for further enhancing the efficiency of planar PVSCs.
Gesehen am 20.11.2018